Mechanical characterisation of the TorPeDO: a low frequency gravitational force sensor. (5th June 2017) - McManus, D J; Forsyth, P W F; Yap, M J; Ward, R L; Shaddock, D A; McClelland, D E; Slagmolen, B J J
Abstract: Newtonian noise is likely to be a future challenge at low frequencies for Advanced LIGO and other second generation gravitational wave detectors. We present the TorPeDO system: a dual torsion pendulum sensor designed to measure local gravitational forces to high precision. Gravitational forces induce a differential rotation between the two torsion beams, which is measured with an optical read-out. Both torsion pendulums have a common suspension point, tunable centre of mass, and resonant frequency. This produces a high level of mechanical common mode noise cancellation. We report on a controls prototype of the TorPeDO system, presenting the frequency response and tuning range of both pendulums. A noise budget and mechanical cross-coupling model for this system are also presented. We demonstrate frequency tuning of the two torsion pendulums to a difference of 4.3 μ Hz.